Photons without borders: quantifying light pollution transfer between territories - Bará, Salvador (2018)
The light pollution levels experienced at any given site generally depend on a wide number of artificial light sources distributed throughout the surrounding territory. Since photons can travel long distances before being scattered by the atmosphere, any effective proposal for reducing local light pollution levels needs an accurate assessment of the relative weight of all intervening light sources, including those located tens or even hundreds of km away. In this paper we describe several ways of quantifying and visualizing these relative weights. Particular emphasis is made on the aggregate contribution of the municipalities, which are -in many regions of the world- the administrative bodies primarily responsible for the planning and maintenance of public outdoor lighting systems.